Unraveling the hepatoprotective effects of blueberries in a hypercaloric diet-induced rat model of prediabetes by metabolomic and transcriptomic approaches. (3rd August 2021) - Nunes, S; Viana, S; Preguiça, I; Alves, A; Fernandes, R; Jarak, I; Carvalho, R; Cavadas, C; Rolo, A; Palmeira, C; Pintado, M; Reis, F
Abstract: Background: We previously described protective effects of blueberry juice (BJ) against hepatic steatosis evolution in a hypercaloric diet-induced rat model of prediabetes; however, the underlying mechanisms, are still scarcely explored. Herein, we aim to elucidate the molecular pathways underpinning BJ hepatoprotection on the dysmetabolism evolution in a rat model of prediabetes. Methods: A rat model of evolutive prediabetes [Male Wistar rats, 8 weeks old] was developed by ingestion of a high-sucrose (HSu, 35%) diet for 9 weeks (W9), supplemented with a high-fat diet (HF, 60%) for further 14 weeks (HSuHF, W23), vs control with standard diet. Half of the animals ( n = 10/group) daily received BJ (25g/Kg BW, orally) between W9 and W23. Along with metabolic characterization, BJ effects on serum and hepatic metabolic surrogates were elucidated using a 1 H NMR based metabolomic approach. Moreover, the liver expression of genes (RT-PCR) involved in insulin signaling, lipid metabolism, inflammatory response and mitochondrial respiration was also explored. Values are means ± S.E.M (ANOVA followed by post-hoc tests). Results: HSuHF+BJ rats restored hepatic levels of betaine and tend to recover the depletion of glutathione content found in HSuHF animals' livers. Moreover, BJ positively affected the hepatic mRNA expression of key enzymes and mediators involved in fatty acid oxidation, insulin signalling, inflammatory response, as well as mitochondrial respiratory chain-related genes, which were all downregulated ( P < 0.05) in HSuHF animals' livers. Conclusions: Altogether, these molecular findings contribute to explain the mechanisms by which BJ elicits protection against hepatic steatosis and mitochondrial dysfunction induced by hypercaloric diets in the frame of prediabetes evolution.